Utilization of Honey as an Extender Material in Cryopreservation of Selincah Fish Sperm (Belontia hasselti) - Danang Yonarta; Retno Cahya Mukti; Agung Riswandi; Rizka Aprilia (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2025)
Problems often encountered in the breeding of selincah fish are that the maturation period of the male and female parent fish sometimes does not occur simultaneously. Reproductive biotechnology can be used to store sperm (sperm cryopreservation). Cryopreservation is a storage technique using a low temperature of -196oC. Extenders and cryoprotectants play an important role in the cryopreservation process. One of the extender materials that can be used is honey. This study was conducted to determine the best dose of honey as an extender material in cryopreserving selincah fish sperm. This study used a completely randomized design with four treatments and three replications. The treatments given were (P0) 100% ringer lactate solution, (P1) 0.25% honey + 99.75% ringer lactate solution, (P2) 0.5% honey + 99.50% ringer lactate solution, and (P3) 0.75% honey + 99.25% ringer lactate solution. The results of the study showed that pre-cryopreservation of selincah fish sperm included a sperm volume of 0.5 mL, sperm pH of 7, moderate sperm consistency, sperm movement duration of 120 seconds with a percentage of motility score of 5 (100%), and sperm viability of 89.50%. The post-cryopreservation study of selincah fish sperm for 14 days of storage showed the best results at P3 (0.75% honey) with a sperm motility score of 4 (90%) and sperm viability of 79.50%. Water quality data during the maintenance of selincah fish broodstock in this study were pH 6.0-7.5 and temperature 25.5 - 28.5oC.